ANALISIS KETERAMPILAN PROSES SAINS SISWA MELALUI PEMBELAJARAN BERBASIS PROYEK PADA MATERI LARUTAN ELEKTROLIT DAN NON-ELEKTROLIT - Dwiki Wahyudi; Lazulva Lazulva (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2021)
This research aimed at knowing the accomplishment of seven indicators of student science process skill after being taught by using Project Based Learning model on Electrolyte and non-Electrolyte Solution lesson. This research was conducted to the tenth-grade students of TLM 2 at Vocational High School of Abdurrab Pekanbaru in the Academic Year of 2019/2020 on Electrolyte and non-Electrolyte Solution lesson. It was a descriptive research. The design of this research was the one shoot case study. Purposive sampling technique was used in this research, and 20 students were the samples. The instruments were essay test and observation sheet. The data analysis result showed that student science process skill after being taught by using Project Based Learning model generally accomplished good category. The highest indicator of student science process skill accomplished by students was in the indicator of communication with 85% percentage based on the test and 90% based on observation sheet.